The Halosphaeriaceae revisited - Jones E. (2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston. The Halosphaeriaceae is a monophyletic group that shares a common ancestor with Microascaceae and, along with the families Graphiaceae, Ceratocystidiaceae, Chadefaudiellaceae and Gondwanamycetacea, is referred to the order Microascales. It constitutes the largest family in Microascales with 63 genera (166 species) and differs from other families in that most species are aquatic (predominantly marine) and characterised by perithecial ascomata, centrum tissue comprising catenophyses, clavate to fusiform asci that generally deliquesce early, hyaline, unicellular to many times septate ascospores usually with appendages. Although approximately 75% of halosphaeriaceous species have been sequenced, their phylogenetic grouping based on morphological features is not supported. This indicates that certain characters have evolved and been lost several times. New sequences have been generated in this study; a phylogenetic analysis based on the 18S and 28S rDNA was run to determine phylogenetic relationships between genera, and pairwise distance of the partial 28S rDNA was calculated. Arenariomyces is a monophyletic genus, which suggests that its ascospore appendage is a good delineating character for the genus. The genus Aniptodera is shown to be polyphyletic; Aniptodera lignatilis is referred to Aniptosporopsis gen. nov. and Aniptodera longispora is referred to Paraaniptodera gen. nov.